2012
DOI: 10.4141/cjps2011-207
|View full text |Cite
|
Sign up to set email alerts
|

Review: Strategies to increase nitrogen use efficiency of spring barley

Abstract: Anbessa, Y. and Juskiw, P. 2012. Review: Strategies to increase nitrogen use efficiency of spring barley. Can. J. Plant Sci. 92: 617–625. Improvement in nitrogen use efficiency (NUE) is important to reduce input costs and the negative impact of excessive N on the environment. This review found that barley growers in western Canada have over the years adopted a number of improved N management strategies including soil testing and adjusting rate of N fertilization accordingly, switching from fall application to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 48 publications
3
33
1
1
Order By: Relevance
“…The N accumulation in plants and grains was in agreement with the reports by Zotarelli et al [50]. Grain N yield increased with the rate of N fertilizer and averaged over cultivars, and grain N yield was 94, 126, and 146 kg ha -1 for the low, moderate, and high N regimes [7]. Mean grain N accumulation was ranged from 12 to 17 and 13 to 18 from maize varieties planted with half and full recommended nitrogen fertilizer application.…”
Section: Shoot and Grain N Accumulation And N Harvest Index Ofsupporting
confidence: 81%
See 2 more Smart Citations
“…The N accumulation in plants and grains was in agreement with the reports by Zotarelli et al [50]. Grain N yield increased with the rate of N fertilizer and averaged over cultivars, and grain N yield was 94, 126, and 146 kg ha -1 for the low, moderate, and high N regimes [7]. Mean grain N accumulation was ranged from 12 to 17 and 13 to 18 from maize varieties planted with half and full recommended nitrogen fertilizer application.…”
Section: Shoot and Grain N Accumulation And N Harvest Index Ofsupporting
confidence: 81%
“…Application of half and full recommended nitrogen fertilizer to maize varieties was given higher shoot nitrogen accumulation of 56 and 881% over maize varieties planted without nitrogen fertilizer application. Similarly, Anbessa and Juskiw [7] found that biomass N yield was increased with the rate of N fertilizer. The correlation coefficients between maize productivity and N accumulated in shoots (leaves, corncobs, straws, and stems) were high [48].…”
Section: Shoot and Grain N Accumulation And N Harvest Index Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The key targets of the NUE research are to increase the proportion of N recovered from the soil (RE N ) and to obtain an enhanced efficiency of utilization of the N taken-up for yield formation (NUtE). Increased N recovery and utilization efficiency may allow growers to maximize yield under a moderate rate of N fertilization instead of the high rate of N fertilization (Anbessa andJuskiw 2012, Bingham et al 2012). If N is applied and not taken up by the crop or immobilized in soil organic N pools, which include both microbial biomass and soil organic matter, is vulnerable to losses from volatilization, denitrification and leaching (Cassman et al 2002).…”
mentioning
confidence: 99%
“…If N is applied and not taken up by the crop or immobilized in soil organic N pools, which include both microbial biomass and soil organic matter, is vulnerable to losses from volatilization, denitrification and leaching (Cassman et al 2002). Only 30-50% of applied nitrogen fertilizer is taken up by crops (Dobermann 2005), hence the improvement in NUE is important to reduce input costs and the negative impact of excessive N on the environment (Snyder 2009, Anbessa andJuskiw 2012). Fertilizer N crop recovery efficiency is driven by three main sets of controls: 1. crop N demand; 2.…”
mentioning
confidence: 99%